TEKNIK BACA MANGOLD TERHADAP KEMAMPUAN MEMBACA PERMULAAN BRAILLE BAGI SISWA TUNANETRA - ARUM LAILATUL F, DEVI (Jurnal Pendidikan Khusus, 2017)
ABSTRACT        This research was based by the low of eliminary braille reading ability which includes reading the letters, syllables and simple words. To overcome these problems used an appropriate technique is Mangold reading technique. The mangold reading technique  was a technique to arrange braille letters using two hands to be able to read by fast and easy hands movement and to be able to minimize error reading the letters which reversed to the other letters. This research aims to determine there is the influence of Mangold reading technique on eliminary braille reading ability of students with visual impairment in SLB-A YPAB Surabaya.         This research used quantitative approach with research type of pre-experimental study and research design one-group-pretest-posttest-design. The subjects of this research numbered 6 students with visual impairment of class 1 SDLB. Technique of collecting data by using observation and test. Data were analyzed using non parametric by Wilcoxon Match Pairs Test.  Based on data analyzed about eliminary braille reading ability of students with visual impairment when before being given treatment (Pre-Test) obtained an average value 50.83 and was given treatment (Post-Test) using Mangold reading technique obtained an average value of  80. From the counting result using Wilcoxon Match Pairs Test it was obtained the value of Z counted = 2.20 was greater than critic value α = 5% is 1.96. Then Ho is rejected and Ha accepted. So, the results of data analysis showed that there was a significant influence Mangold reading technique on eliminary reading ability of students with visual impairment.   Keywords: Mangold Reading Technique, Eliminary Braille Reading Ability